Metabolic Parkinson’s disease - Invernizzi, Federica; Ciocca, Lorenzo; Contaldi, Elena; Inverso, Donato; Calandrella, Daniela; Mignone, Francesco; Barichella, Michela; Isaias, Ioannis Ugo; Pezzoli, Gianni (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease (PD) is a neurodegenerative disorder primarily characterized by the loss of dopaminergic neurons in the substantia nigra. While most cases are sporadic, there is growing evidence of a link between PD and metabolic dysfunctions such as type 2 diabetes mellitus, obesity, and metabolic syndrome. Proposed pathogenic mechanisms underlying this overlap include insulin resistance and chronic inflammation. Similar patterns of cellular damage are observed in both metabolic disorders and PD, including mitochondrial dysfunction, impaired autophagy, oxidative stress, endoplasmic reticulum stress, and gut microbiota alterations. Given the current lack of disease-modifying therapies for PD, there is increasing interest in interventions traditionally used to treat metabolic conditions, such as lifestyle and dietary modifications. Notably, antidiabetic drugs like metformin and incretin mimetics have shown beneficial effects in PD due to their neuroprotective and anti-inflammatory properties, their ability to restore insulin sensitivity, and their role in reducing neuronal susceptibility to toxic insults, as demonstrated in both preclinical and clinical studies. Conversely, traditionally antiparkinsonian drugs such as bromocriptine have long been approved for improving glycemic control in diabetes. This cross-efficacy between drugs used for the two conditions may indirectly support the hypothesis of a shared pathogenesis. A deeper understanding of the connections between metabolic disorders and PD could pave the way for novel preventive and therapeutic strategies.